Ocean acidification but not warming alters sex determination in the Sydney rock oyster, Saccostrea glomerata. Issue 1872 (14th February 2018) - Parker, Laura M.; O'Connor, Wayne A.; Byrne, Maria; Dove, Michael; Coleman, Ross A.; Pörtner, Hans-O; Scanes, Elliot; Virtue, Patti; Gibbs, Mitchell; Ross, Pauline M.
Abstract : Whether sex determination of marine organisms can be altered by ocean acidification and warming during this century remains a significant, unanswered question. Here, we show that exposure of the protandric hermaphrodite oyster, Saccostrea glomerata to ocean acidification, but not warming, alters sex determination resulting in changes in sex ratios. After just one reproductive cycle there were 16% more females than males. The rate of gametogenesis, gonad area, fecundity, shell length, extracellular pH and survival decreased in response to ocean acidification. Warming as a sole stressor slightly increased the rate of gametogenesis, gonad area and fecundity, but this increase was masked by the impact of ocean acidification at a level predicted for this century. Alterations to sex determination, sex ratios and reproductive capacity will have flow on effects to reduce larval supply and population size of oysters and potentially other marine organisms.